Impact of vitamin D supplementation on cognitive impairment in elderly individuals with hypertension - Lili Tan; Hongyan Li; Linya Zhao (Frontiers in Neurology)
BackgroundOlder adults frequently experience vitamin D deficiency, which has been linked to both cognitive decline and hypertension. However, evidence on whether correcting vitamin D insufficiency can improve recognition memory and blood pressure (BP) control in this population remains inconclusive.ObjectiveTo evaluate the association between vitamin D supplementation and improvements in cognitive function and BP among older adults with hypertension and mild cognitive deficits.MethodsWe conducted a retrospective review of patient records from individuals aged ≥65 years who had documented hypertension, baseline 25-hydroxyvitamin D (25(OH)D) levels < 30 ng/mL, and mild cognitive impairment (Montreal Cognitive Assessment [MoCA] < 26) or subjective cognitive complaints. Patients were categorized into two groups based on recorded vitamin D supplementation (≥5,000 IU/day for ≥6 months vs. no or minimal supplementation). Recognition memory, global cognition (MoCA), systolic and diastolic BP, and serum 25(OH)D levels were compared between groups.ResultsAmong 153 eligible records, those in the Supplemented group showed greater gains in recognition memory (+3.1 ± 2.4 vs. +1.2 ± 2.0 points; p = 0.01) and a larger decrease in systolic BP (−12.8 ± 7.2 vs. −7.1 ± 6.8 mmHg; p = 0.03). Sensitivity analyses confirmed these benefits. For instance, in adjusted multivariable regression, recognition memory improved by an additional +1.8 points (95% CI 0.9–2.7; p = 0.002) and systolic BP fell by −10.7 mmHg (p = 0.01) in the Supplemented group. Multivariable regression and propensity-score-matched analyses yielded comparable cognitive and blood-pressure benefits. Stratified analyses indicated stronger responses in those with MoCA < 22 (+2.9 points in recognition memory; p = 0.01) and in participants with baseline 25(OH)D < 20 ng/mL (+2.8 points; p = 0.003). Both men and women derived similar cognitive and BP benefits. Mild hypercalcemia occurred in 3.8% of supplemented patients vs. 1.3% of comparisons.ConclusionsIn this retrospective cohort, vitamin D supplementation was associated with notable improvements in recognition memory, global cognition, and systolic BP among older adults with hypertension and mild cognitive deficits. These findings highlight the potential clinical benefits of correcting vitamin D insufficiency in this high-risk population, warranting further investigation in prospective trials.